Predation by carpet pythons (Morelia spilota) is an important cause of mortality in a free‐living koala (Phascolarctos cinereus) population in South East Queensland. Issue 9 (16th July 2019) - Robbins, Amy; Loader, Joanne; de Villiers, Deidre; Beyer, Hawthorne L.; Hanger, Jonathan
Abstract : Koalas ( Phascolarctos cinereus) are experiencing significant declines across the northern part of their range. However, unbiased, population‐level estimates of mortality are rarely reported, as it's difficult to quantify causes of mortality robustly in this cryptic species. We aimed to determine the relative importance of carpet python ( Morelia spilota ) predation in a free‐living koala population and describe the characteristic pathological findings during necropsy. In total, 503 koalas were captured, underwent veterinary examination and telemetric tagging, and were monitored after release over a four‐year period. Mortalities were detected when activity data reported by K‐Tracker® biotelemetry collars indicated low or zero activity, or during routine field monitoring events. Experienced koala veterinarians performed thorough, standardised necropsy examinations on retrieved carcasses to determine causes of death. The three, sometimes subtle, cardinal signs used to definitively diagnose carpet python‐caused deaths of koalas were a U‐shaped primary bite site, slicking of the fur by python saliva (particularly around the face), and diffuse, uniform pulmonary congestion. We found that carpet pythons were important predators of koalas, second only to wild dogs (dingoes and dingo hybrids ( Canis familiaris dingo )), accounting for 11.6% of predation deaths and 7.2% of total deaths. Less than half (38%) of the koalas killed by carpet pythons were ingested. Though carpet pythons are known predators of koalas, their relative importance as a cause of mortality hasn't previously been recognised. Population viability analyses and conservation management plans benefit from robust cause‐of‐death data collected during longitudinal monitoring studies, requiring telemetry methods that facilitate rapid detection of mortalities.